2012
DOI: 10.1128/jb.06643-11
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of an Efficient Antibiotic-Producing Industrial Strain of Saccharomonospora azurea, SZMC 14600

Abstract: Although certain rare actinomycetes have been recognized as prolific sources of bioactive natural products, their potential for producing biologically active metabolites still remains unexplored. With the aim of gaining global insights into the genetic background and the metabolic capability of Saccharomonospora azurea SZMC 14600, whole-genome sequencing was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Genome sequencing methods of S. azurea SZMC 14600 have been described previously (Csepregi et al 2012 ). Comparative genome analysis was carried out within the Integrated Microbial Genomes Database Expert Review (IMG-ER) system ( https://img.jgi.doe.gov/cgi-bin/w/main.cgi ) (Markowitz et al 2009 , 2012 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome sequencing methods of S. azurea SZMC 14600 have been described previously (Csepregi et al 2012 ). Comparative genome analysis was carried out within the Integrated Microbial Genomes Database Expert Review (IMG-ER) system ( https://img.jgi.doe.gov/cgi-bin/w/main.cgi ) (Markowitz et al 2009 , 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Primycin was first described in 1954 to be produced by Streptomyces primycini , and thereafter by Micromonospora galeriensis , but none of these species was validly published (Szabó et al 1976 ; Vályi-Nagy et al 1954 ). In recent times, only S. azurea is known to has the ability to produce primycin (Csepregi et al 2012 ; Klenk et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative in vitro re-investigation of the efficacy of primycin clearly demonstrated that the antibiotic possesses high activity against the most frequent Gram-positive pathogens including some multi-drug resist-ant strains, without remarkable resistance development [8]. To get a deeper insight into the bioactive natural products metabolism of S. azurea SZMC 14600 wholegenome sequencing was performed [5]. The genome project clearly demonstrated that S. azurea is a prolific source of structurally diverse secondary metabolites, however, the in silico information was not tied to products in the laboratory until now.…”
Section: Introductionmentioning
confidence: 99%
“…mesenteroides Strain J18, sequence accession CP003101 [63] Paenibacillus peoriae Strain KCTC 3763 T , sequence accession AGFX00000000 [64] Pediococcus acidilactici MA18/5M, sequence accession AGKB00000000 [65] Pediococcus claussenii ATCC BAA-344 T , sequence accession CP003137 (chromosome), CP003138 (pPECL-1), CP003139 (pPECL-2), CP003140 (pPECL-3), CP003141 (pPECL-4), CP003142 (pPECL-5), CP003143 (pPECL-6), CP003144 (pPECL-7), CP003145 (pPECL-8) [66] Staphylococcus aureus M013, sequence accession CP003166 [67] Staphylococcus aureus subsp. aureus TW20, sequence accession FN433596 [68] Weissella confusa LBAE C39-2, sequence accession CAGH00000000 [69] Phylum Actinobacteria Corynebacterium casei, sequence accession CAFW01000001 to CAFW01000106 [70] Corynebacterium glutamicum, sequence accession AGQQ00000000 [71] Leucobacter chromiiresistens, sequence accession AGCW00000000 [72] Mycobacterium abscessus, sequence accession AGQU00000000 [73] Propionibacterium acnes ST9, sequence accession CP003195 [74] Propionibacterium acnes ST22, sequence accession CP003196 [74] Propionibacterium acnes ST27, sequence accession CP003197 [74] Saccharomonospora azurea SZMC 14600, sequence accession AHBX00000000 [75] Streptomyces sp. Strain TOR3209, sequence accession AGNH00000000 [76] Streptomyces sp.…”
Section: Phylum Firmicutesmentioning
confidence: 99%